The Clinical Benefit of Bevacizumab in Metastatic Colorectal Cancer Is Independent of K‐ras Mutation Status: Analysis of a Phase III Study of Bevacizumab with Chemotherapy in Previously Untreated Metastatic Colorectal Cancer - Hurwitz, Herbert I.; Yi, Jing; Ince, William; Novotny, William F.; Rosen, Oliver (The oncologist (Dayton, Ohio), 2009)
Purpose. Mutations of the K‐ras gene were identified as a prognostic marker in metastatic colorectal cancer (mCRC). In addition, emerging data suggest that K‐ras mutations are a negative predictor of clinical benefit from anti–epidermal growth factor receptor treatment in mCRC. Previously reported data suggest that the longer overall survival (OS) observed with bevacizumab treatment in mCRC is independent of alterations in the Ras/Raf/Mek/Erk pathway. We conducted additional analyses to better describe the clinical benefit of bevacizumab treatment in mCRC relative to K‐ras mutation status. Patients and Methods. Additional statistical analyses were done with data from K‐ras mutation analyses in 230 patients who were treated with irinotecan, fluorouracil, and leucovorin (IFL) in combination with either bevacizumab or placebo in a randomized phase III study. Following microdissection, tissue was subject to DNA sequencing to identify K‐ras mutations in codons 12 and 13. Hazard ratios for the bevacizumab group relative to the control group were estimated from an unstratified Cox regression model. The median progression‐free survival (PFS), OS times, and objective response rates were compared. Results. K‐ras status was assessed in 230 patients (28.3%). The median PFS was significantly longer in bevacizumab‐treated patients with wild‐type (wt)‐ (13.5 versus 7.4 months; hazard ratio 0.44, p < .0001) and mutant (m)‐K‐ras (9.3 versus 5.5 months; hazard ratio 0.41, p = .0008). A significantly higher response rate for IFL plus bevacizumab was observed only in wt‐K‐ras patients (60.0% versus 37.3%, p = .006) compared with 43.2% versus 41.2% in the m‐K‐ras group. Conclusion. Bevacizumab provides significant clinical benefit in patients with mCRC expressing either mutant or wild‐type K‐ras. This study describes parameters of clinical benefit of bevacizumab treatment in metastatic colorectal cancer patients relative to K‐ras mutation status. Bevacizumab resulted in a statistically significant longer median progression‐free survival time in patients with both wild‐type and mutant K‐ras, suggesting significant clinical benefit regardless of K‐ras status.